Journeys - Seeman, Annette (West Australian Quilters' Association Inc., 2012)
'Journeys' is a quilt exhibited by the artist Annette Seeman as part of the event stitched & bound 2012, a juried exhibition of contemporary quilts, presented by the Western Australian Quilters' Association.